Range Extensions and Taxonomic Notes on Atlantic Myxasteridae (Velatida; Asteroidea) - Mah, Christopher L.; Mercier, Annie; Hamel, Jean-Francois; Nizinski, Martha (Zootaxa, 2012)
Newly collected specimens of the Atlantic Myxaster sol and a further record of Pythonaster atlantidis add to the knownoccurrence records and the morphological variation of these rarely encountered species. Distribution data suggests thatboth M. sol and P. atlantidis are pan-Atlantic species and are similar to other widely distributed deep-sea asteroid species.Re-examination of the type of Myxaster perrieri further supports its placement within Myxaster and not Pythonaster as has been recently reported.